Implementasi Model Sistem Dinamik Terhadap Analisis Tingkat Kemacetan Lalu Lintas - Irsyad Baihaqi Lubis; M.R Syahputra; Syawaluddin Syawaluddin; Syahriol Sitorus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Overcoming existing traffic congestion is something that many people hope for, especially people who are always trapped in these traffic problems. One of the methods used to reduce traffic congestion is the dynamic system approach. This method analyses and simulates the problem by determining the causal variables. The analysis was conducted using a causal loop diagram model which was then simulated with a stock flow diagram model using Ventana Simulation (Vensim) software. The results showed that there was a decrease in the average level of traffic congestion on Jalan Setia Budi with an initial condition of 1.06% to 0.71%. This 32% decrease has an impact on traffic conditions that are busy without any delays in travel time on Jalan Setia Budi.